The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1109/ojcoms.2020.3026952
|View full text |Cite
|
Sign up to set email alerts
|

Joint Channel and Antenna Modeling for Magnetic Induction Communication in Inhomogeneous Media

Abstract: Magnetic induction communication (MIC) demonstrates high penetration efficiency and low propagation loss in extreme environments. It is used in underground and underwater environments to enable critical applications that cannot be achieved by using terrestrial wireless techniques. This paper studies the channel and antenna modeling for MIC in inhomogeneous environments, where a transmitter and a receiver are in two different media. This problem finds a large number of practical applications such as communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For MI, the Inductive Wireless Power Transfer (IWPT) system will be implemented following the model proposed by Al Sinayyid et al [7] through the use of IoUT Multi Coil nodes. Li et al [8] developed Multi Coil nodes that can adapt to the direction of the incoming signal, while Guo et al [36] enhanced Multi Coil transmission by introducing spatial diversity. Kisseleff et al [48] revealed the possibility of electromagnetic wave propagation in UWSN through the ocean floor layers.…”
Section: Transmission Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For MI, the Inductive Wireless Power Transfer (IWPT) system will be implemented following the model proposed by Al Sinayyid et al [7] through the use of IoUT Multi Coil nodes. Li et al [8] developed Multi Coil nodes that can adapt to the direction of the incoming signal, while Guo et al [36] enhanced Multi Coil transmission by introducing spatial diversity. Kisseleff et al [48] revealed the possibility of electromagnetic wave propagation in UWSN through the ocean floor layers.…”
Section: Transmission Methodsmentioning
confidence: 99%
“…In addition to utilizing metal materials to propagate MI transmission signals in air and soil environments, propagation techniques using Inhomogeneous Media have proven successful in [36]. To enhance the induction transfer coefficient, optimization of the coupling mechanism is performed [37].…”
Section: B Magnetic-inductionmentioning
confidence: 99%
See 1 more Smart Citation